If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(p + -4) + 4 = 2p Reorder the terms: 5(-4 + p) + 4 = 2p (-4 * 5 + p * 5) + 4 = 2p (-20 + 5p) + 4 = 2p Reorder the terms: -20 + 4 + 5p = 2p Combine like terms: -20 + 4 = -16 -16 + 5p = 2p Solving -16 + 5p = 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -16 + 5p + -2p = 2p + -2p Combine like terms: 5p + -2p = 3p -16 + 3p = 2p + -2p Combine like terms: 2p + -2p = 0 -16 + 3p = 0 Add '16' to each side of the equation. -16 + 16 + 3p = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 3p = 0 + 16 3p = 0 + 16 Combine like terms: 0 + 16 = 16 3p = 16 Divide each side by '3'. p = 5.333333333 Simplifying p = 5.333333333
| -1/3h=6 | | 33-9x^2+24x=33 | | 2(w+3)=14 | | N=9/8Q+36 | | (5x^2+8x)(25x^2-5x-2)=0 | | x/11-3=-2 | | x^2+27x+496=0 | | -3x-12=-4x-3 | | 7/8x=4 | | 5x+24=29 | | 2x/7 | | -5x+19=-6 | | -102=6(1+3m) | | x+23=30 | | x+32=30 | | 192=8x+12x | | -20=4(2x-1)-8 | | -28r+35=175 | | 4x(3x^3-2x+5)=0 | | 4(5-2)=52 | | 4x-17=3(x-4) | | 7w-10=6w+4 | | 6d+13-8d+10=8d | | -18+9y=9 | | 9x-11=2x-39 | | 3(2x+4)=-4x-8 | | 3y+4-y=16 | | 48=4(x+3)-8 | | 3x^2-54=9x | | 7n+4=11n-28 | | 0,25x+174,95=300 | | -4x-8=4(3x+2) |